Dentigerous Cyst containing a Supernumerary Tooth below Floor of Maxillary Sinus - Rawat, Amit; Newaskar, Vilas; Agrawal, Deepak; Sharma, Divashree; Singh, Charanpreet (Journal of Orofacial Research, 2012)
Dentigerous cyst is considered to be a developmental odontogenic cyst that surrounds the crown of impacted, unerupted or supernumerary teeth. This case report presents adentigerous cyst associated with a supplemental supernumerary tooth in right anterior maxillary region. Enucleation of the pathology along with the impacted supernumerary tooth wasdone. The patient has remained asymptomatic since 6 months and there is no evidence of recurrence.